2004
DOI: 10.1192/bjp.184.3.216
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–environment interaction in schizophrenia-spectrum disorder

Abstract: Adoptees at high genetic risk are significantly more sensitive to adverse v. 'healthy' rearing patterns in adoptive families than are adoptees at low genetic risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
181
0
11

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(198 citation statements)
references
References 24 publications
6
181
0
11
Order By: Relevance
“…There is evidence from animal work that neuregulin-1 and DISC1 may modify the consequences of prenatal immune activation 107,108 and that neuregulin 1 may modify the effect of exposure to social defeat. 107 There is also evidence from human studies that COMT may modify the effects of adolescent exposure to cannabis, 15 that individuals at high genetic risk for schizophrenia are particularly sensitive to the adverse effects of a negative family rearing environment, 109 and the effect of urbanicity is mediated by genetic liability to psychosis. 110 The urbanicity studies found that 60% to 70% of those in the sample who developed schizophrenia did so as a result of the synergistic action between urban dwelling and familial liability to psychosis.…”
Section: Gene-environment Intreractionmentioning
confidence: 99%
“…There is evidence from animal work that neuregulin-1 and DISC1 may modify the consequences of prenatal immune activation 107,108 and that neuregulin 1 may modify the effect of exposure to social defeat. 107 There is also evidence from human studies that COMT may modify the effects of adolescent exposure to cannabis, 15 that individuals at high genetic risk for schizophrenia are particularly sensitive to the adverse effects of a negative family rearing environment, 109 and the effect of urbanicity is mediated by genetic liability to psychosis. 110 The urbanicity studies found that 60% to 70% of those in the sample who developed schizophrenia did so as a result of the synergistic action between urban dwelling and familial liability to psychosis.…”
Section: Gene-environment Intreractionmentioning
confidence: 99%
“…Environmental factors are also important in the development of psychotic disorders, which is based on recent research of the association between psychotic disorders and cannabis use, childhood trauma and urbanicity (Cougnard et al, 2007). A study of Finnish adoptees found evidence for a genotypeenvironment interaction in schizophrenia-spectrum disorders (Tienari et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that gene -environment interactions may be components of the overall risk. 4 Schizophrenia is thus largely genetically mediated but not genetically determined.…”
Section: Family Studies: Does Risk Aggregate In Relatives?mentioning
confidence: 99%